2009
DOI: 10.1002/arch.20321
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of two nicotinic acetylcholine receptor subunits from Liposcelis bostrychophila Badonnel (Psocoptera: Liposcelididae)

Abstract: Two nicotinic acetylcholine receptor (nAChR) subunit genes, Lbalpha1 and Lbalpha8, were isolated and characterized from psocid, Liposcelis bostrychophila Badonnel, using the rapid amplification of cDNA ends (RACE) technique. They are the first two nAChR family members isolated from the insect order of Psocoptera. The full-length cDNAs of Lbalpha1 (GenBank accession number: EU871527) and Lbalpha8 (EU871526) consist of 2,025 and 1,763 nucleotides, respectively, and an open reading frame of 1,644 and 1,608 bp enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…We identified a total of four types of target-site sequences related to different classes of insecticides by the BLASTx searches for genes in the NCBI database. Modification of AChE can lead to insensitivity to a variety of organophosphate and carbamate based compounds [38] . In our study, one unigene of 2,052 bps in length was identified as containing the ace gene, and it showed 99% similarity with a gene cloned and characterized from the same L. bostrychophila line [38] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified a total of four types of target-site sequences related to different classes of insecticides by the BLASTx searches for genes in the NCBI database. Modification of AChE can lead to insensitivity to a variety of organophosphate and carbamate based compounds [38] . In our study, one unigene of 2,052 bps in length was identified as containing the ace gene, and it showed 99% similarity with a gene cloned and characterized from the same L. bostrychophila line [38] .…”
Section: Discussionmentioning
confidence: 99%
“…Modification of AChE can lead to insensitivity to a variety of organophosphate and carbamate based compounds [38] . In our study, one unigene of 2,052 bps in length was identified as containing the ace gene, and it showed 99% similarity with a gene cloned and characterized from the same L. bostrychophila line [38] . The cases of knockdown resistance to pyrethroids, DDT resistance have been documented through reduced sodium channel sensitivity [39] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that expression of different nAChR subunits varies across development and this has been shown in two α-subunits of Liposcelis bostrychophila (Tang et al, 2009). From a control perspective, an ideal drug would be effective against all life stages of tick development.…”
Section: Discussionmentioning
confidence: 99%
“…For 5′‐ and 3′‐RACE, cDNA was synthesized according to the manufacturer's protocol [SMART™ kit (Clontech Laboratories, Inc. (Takara Bio company), Delian, China); Tang et al, ]. Specific primers for 5′‐RACE (SpoexGP‐5RA, SpoexGP‐5RB, and SpoexGP‐5RC) and 3′‐RACE (SpoexGP‐3FA, SpoexGP‐3FB, and SpoexGP‐3FC; Table ) were synthesized based on the cDNA sequence of the PCR fragment.…”
Section: Methodsmentioning
confidence: 99%